A Systematic Assessment of the Spatiotemporal Evolution of Fault Activation Through Induced Seismicity in Oklahoma and Southern Kansas. Issue 12 (13th December 2017) - Schoenball, Martin; Ellsworth, William L.
Abstract: Much of Oklahoma and southern Kansas has seen widespread seismic activity in the last decade that is attributed to large‐scale wastewater disposal into the Arbuckle group. Using a waveform‐relocated earthquake catalog, we perform a systematic study of the activity on several hundreds of identified faults. We use 93 sequences with at least 30 events for a detailed analysis of their spatiotemporal evolution. For most awakened faults, seismicity tends to initiate at shallower depth and migrates deeper along the faults as the sequence proceeds. No major sequence starts with the largest earthquake, and many sequences initiate months before they rise to peak activity. We study temporal clustering as a means to quantify earthquake interactions. Some sequences show no temporal clustering similar to Poissonian background seismicity but at much higher rate than the natural background. Other sequences exhibit strong temporal clustering akin to main shock‐aftershock sequences. We conclude that once initiated by anthropogenic forcing, portions of the activated faults in the Oklahoma/Kansas area are close enough to failure to continue failing through earthquake interactions. In many sequences, including those with the largest earthquakes, seismicity continues within the previously activated region rather than by growing the activated area. Therefore, monitoring seismicity with a low magnitude threshold and high location precision has the potential to detect minor activity as it initiates failure on specific faults and thus provide time to take actions to mitigate the occurrence of potentially damaging earthquakes. Plain Language Summary: Much of Oklahoma and southern Kansas has experienced an unprecedented level of earthquake activity in the last 8 years that is attributed to large‐scale wastewater disposal. Using a catalog of precise earthquake locations, we perform a systematic study of the earthquake activity on several hundred previously unknown faults. No major earthquake sequence starts with the largest earthquake, and many sequences initiate months before they rise to peak activity. Virtually all of the earthquakes occur in the crystalline basement, typically four or more kilometers below the wastewater injection zone. For most awakened faults, seismicity migrates to deeper depth along the faults as the sequence proceeds. Once initiated by elevated pressure from wastewater disposal, natural conditions on reactivated faults in the Oklahoma/Kansas area promote further earthquakes and release of stored tectonic energy. Monitoring seismicity with high sensitivity and location precision has the potential to identify minor seismic activity early on. This knowledge may provide time to take mitigating actions to reduce the potential for damaging earthquakes. Key Points: Many sequences initiate months before rising to peak activity, and none starts with an earthquake larger than M 3.6 Sequences propagate along faults through a combination of earthquake interactions and anthropogenic stressing Improved monitoring has the chance to anticipate increasing potential for strong earthquakes